mfherbst/look4bas v0.3.0 ... - Herbst, Michael F. (Zenodo, 2019)
Features Support for more download formats: Gaussian94 CFOUR (only experimental support) NWChem ORCA pyscf Q-Chem Turbomole (only experimental support) Misc python >= 3.5 is now required ...